Application of the GeoGebra Graphing Calculator in Mathematics Learning to Improve Students' Mathematical Competence - Malik, Fatus Atho'ul; Hidayatullah, Bagus; Setiawan, Wahyu; Amalliyah, Nor; Nurwahid, Mohammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
One concrete step in improving students' mathematical competencies in modern education is through the application of interactive digital learning media. The GeoGebra Graphing Calculator application is an interactive and user-friendly digital learning tool. This research uses classroom action research. The subjects of this study are 20 students from class XI at MA Tarbiyatus Shibyan Lamongan. The classroom action research was conducted in two cycles. In each cycle, students were given worksheets on the topic of linear programming. In Cycle I, students completed the worksheets manually, while in Cycle II, students were introduced to the learning media and used the GeoGebra Graphing Calculator in completing the worksheets. The results obtained from this study using the T-Test (Paired Samples Statistic) show a p-value of ), indicating that the application of the GeoGebra Graphing Calculator in mathematics learning has an impact on improving students' mathematical competencies. Based on the average scores in each cycle, it is also evident that the use of the GeoGebra Graphing Calculator has an effect, as students' competencies improved from a moderate level with an average of 73.75% to a high level with an average of 89.06% after the application of the GeoGebra Graphing Calculator.